CURRENT TRENDS IN UNNATURAL FEMALE DEATHS IN CENTRAL INDIA (Journal of Forensic Medicine & Toxicology, 2024)
To know the epidemiological aspects, pattern and medico legal aspects of Unnatural female deaths in Nagpur, Maharashtra, we have conducted an autopsy based cross sectional study on 511 cases of female deaths in the Department of Forensic Medicine during January 2011 to September 2012. Most of the females were young housewives, belonging to lower socioeconomic class. Most common cause of death was burns followed by mechanical trauma. 60.08% of the total deaths were accidental in nature followed by 35.81% suicidal. Most common manner and cause of death in alleged dowry victims was suicide and burns respectively.
Keywords: Unnatural; Female Deaths; trends; Dowry,; Burns